Computer Vision Syndrome Among Computer Users in Muzaffarabad, Azad Jammu and Kashmir (AJK) - Qaim Ali Khan, Muhammad Tahir, Yasir Iqbal, Nauroz Fatima, Qurat Ul Ain Ghazanfar, Benish Ali (Journal of Islamic International Medical College, 2025)
OBJECTIVE: To determine the prevalence of computer vision syndrome among the computer users in Muzaffarabad, AJK.